Bronius Liesis-Naktis - Jurkutė, Mingailė (Genocidas ir rezistencija, 2019)
Although “the life of Salomėja Nėris is better documented than that of any other Lithuanian woman (and better than that of any other writer)”, this is far from meaning that everything is known about her biography. On the contrary, it sometimes seems that her image, the almost mythical figure of the poet, shaped by the times, hinders the recognition of Nėris as a real person, a historical personality. We will probably never know exactly why this active member of the Lithuanian Catholic Federation Ateitis suddenly embraced leftist ideas, nor will we ever know what her true attitude to Soviet reality was, especially after the deportations in June 1941. Perhaps she herself would not have been able to give an unequivocal answer.